CO2 Conversion to Acetic Acid by Acetogen-Enriched Microbial Inocula with H2 Supplied by In-Situ Zero-Valent Metal Oxidation - Samanides, Charis G. (My University, 2025)
In the last decades, anthropogenic carbon dioxide (CO2) emissions have increased dramatically, leading to excessive CO2 levels in the atmosphere. This rise in CO2 concentration has contributed significantly to global warming. For this reason, the European Union (EU) and the scientific community have been actively seeking solutions. This study presents an innovative, cost-effective, and sustainable solution for CO2 mitigation. This gas can be bioconverted into acetic acid by a mixed microbial consortium in a system supplemented with solid metals (zero-valent iron – Fe⁰, magnesium – Mg⁰, and waste iron – FeW) under mild, anaerobic, and carbonated conditions. The innovation focuses on producing the necessary H₂ gas in-situ - which serves as an electron donor and facilitates biological reactions - via the oxidation of metals to eliminate the reliance on external H2 supply.
Keywords: Acetic acid; Βioethanol; CO2 utilization; Iron oxidation derived hydrogen; Magnesium ribbon; Methanogenesis inhibition; ZVI